Ranunculus schmalhausenii (section Batrachium, Ranunculaceae), a neglected water crowfoot endemic to Fennoscandia-a case of rapid hybrid speciation in postglacial environment of North Europe - Bobrov, Alexander A.; Zalewska-Gałosz, Joanna; Jopek, Magdalena; Movergoz, Ekaterina A. (Zenodo, 2015)
Bobrov, Alexander A., Zalewska-Gałosz, Joanna, Jopek, Magdalena, Movergoz, Ekaterina A. (2015): Ranunculus schmalhausenii (section Batrachium, Ranunculaceae), a neglected water crowfoot endemic to Fennoscandia-a case of rapid hybrid speciation in postglacial environment of North Europe. Phytotaxa 233 (2): 101-138, DOI:10.11646/phytotaxa.233.2.1, URL: http://dx.doi.org/10.11646/phytotaxa.233.2.1